Factors Affecting the Performance of Labour in Nigerian Construction Sites - Fagbenle , Olabosipo I.; Ogunde, Ayodeji O.; Owolabi , James D. (Mediterranean Journal of Social Sciences, 2011)
The paper identified some factors perceived to be negatively affecting the performance of construction labour and also examinedhow these factors vary from site to site in the Nigerian construction industry. To achieve this, structured questionnaires were administeredon contractors and labour (operatives) on forty construction sites in the study area to sample their opinions. A Likert statistical techniquewas employed for the analysis in this perspective. The result indicated that unfair wages (RI = 0.89), negative influencing factors (RI =0.85) and lack of motivation (RI = 0.79) were ranked high by the labour while the contractors ranked lack of training (RI = 0.84),poor communication (RI = 0.79) and inclement weather (RI = 0.71) as being affecting the performance labour in this respect. It wasrecommended, among other things, that contractors must study the peculiarities of their workers and identify their main motivators.